Global Trends and Emerging Challenges in Occupational Skin Disease Research: A Comprehensive Bibliometric and Science Mapping Analysis - Yuridian Purwoko, Reza; Ferianasari, Ineke Winda; Aryanti, Evy; Wiyono, Nanang; Zaki, Shifa Nurzahra (Journal La Medihealtico, 2024)
Occupational Skin Diseases (OSDs) represent a significant global health issue. This study aims to analyze OSD research trends from 2014 to 2023 through a comprehensive bibliometric analysis. The search was carried out in the Scopus database using keywords: "occupational skin disease" OR "work-related skin disease" OR "occupational dermatosis". A total of 491 documents were analyzed using VOSviewer and Biblioshiny. The results show an increase in publications with a peak in 2021, dominated by developed countries such as Germany and the United States, but the contribution of developing countries is starting to be seen. The focus of research shifted from classic contact dermatitis to the issue of COVID-19 and the use of personal protective equipment. The University of Osnabrück and the journal Contact Dermatitis are the main contributors. The analysis uncovered gaps in longitudinal research, insufficient research on the informal sector, and limited interventions in developing countries. Future research is suggested to focus on innovative prevention strategies, climate change impacts, and the utilization of new technologies, with an emphasis on international collaboration. This study highlights the importance of OSD research's adaptation to new challenges in the workplace and the need for a more inclusive global approach.